Chemical nature of soil humified fractions and their bioactivity - Canellas, Luciano Pasqualoto; Façanha, Arnoldo Rocha (Pesquisa Agropecuaria Brasileira, 2004)
The aim of this work was to evaluate the humus composition from an Ultisol from Campos dos Goytacazes, RJ, Brazil. Soil samples of four depths (0–0.05, 0.05–0.10, 0.10–0.20 and 0.20–0.40 m) and its chemical nature were analysed by elemental composition, E4/E6 ratios and Fourier transformed infrared spectroscopy. The bioactivity of these humified substances was evaluated through their action on maize root growth and H+-ATPase activity of root's microsomes. In topsoil, the content of high condensed alkaline soluble humic substances is greater than that found in the subsuperficial layers. The chemical nature of humic and fulvic acids also varied with the soil depth. The humic acids isolated from the soil samples exhibited higher bioactivity compared with the fulvic acids. Moreover, the results suggest that more condensed humic substances can promote highest stimulation of the microsomal H+-ATPases from maize roots. These data reinforce the concept that the activity of the H+ pumps can be used as a biochemical marker for evaluation of humic substances bioactivity.